2021
DOI: 10.1177/0091450921993821
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Politics in Policy Discourse: The Debate Over Safe Injection Sites in Philadelphia, Pennsylvania

Abstract: Safe injection sites are spaces where people who inject drugs can do so under the supervision of staff at the sites who attempt to revive them if they overdose. Public officials in Philadelphia, Pennsylvania, have proposed the sites as a means to reduce opioid overdose deaths in the city, a policy proposal that has been politically and legally contested. This article uses the Narrative Politics model to elucidate the concerns, values, and aspirations of the competing narratives in the public discourse over saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Although sites that exist in this fashion have operated successfully for over three decades in Europe, and for two decades in Australia and in Canada, the legality of OPSs in the USA has been a matter of intense debate [ 5 , 6 ]. OPSs attract high-risk drug users and show positive outcomes in decreasing overdose fatalities, infectious disease spread, and public consumption, while also improving public amenity, increasing safe-injecting practices, promoting effective treatment methods, and yielding cost savings by preventing blood-borne infections and fatal overdoses.…”
Section: Introductionmentioning
confidence: 99%
“…Although sites that exist in this fashion have operated successfully for over three decades in Europe, and for two decades in Australia and in Canada, the legality of OPSs in the USA has been a matter of intense debate [ 5 , 6 ]. OPSs attract high-risk drug users and show positive outcomes in decreasing overdose fatalities, infectious disease spread, and public consumption, while also improving public amenity, increasing safe-injecting practices, promoting effective treatment methods, and yielding cost savings by preventing blood-borne infections and fatal overdoses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Canadian newspapers most commonly published health perspectives on harm reduction, and only rarely involved a criminal justice frame (Wild et al, 2019). In analyzing media coverage and official statements surrounding the proposed Safehouse facility in Philadelphia, Lofaro and Miller (2021) found that the harm reduction narrative was largely superseded by NIMBY concerns, which ultimately derailed the proposal.…”
Section: Framing Drug Policy and The Mediamentioning
confidence: 99%
“…For instance, research suggests that personal stories (i.e., anecdotal evidence) may be more compelling to respondents than statements about scientific research evidence (Norris & Mullinix, 2020). Research on media coverage has found multiple different narratives that could be tapped by proposals for these facilities (Lofaro & Miller, 2021), any of which may have unique influences on support levels. Similarly, the type of individual conveying the message may influence how the message is received (e.g., a medical doctor vs. a police chief vs. a former drug user).…”
Section: Limitationsmentioning
confidence: 99%
“…While some groups outright oppose harm reduction services, in part due to the perception that they enable drug use, others see the need for these programs but ascribe to “not in my backyard” (NIMBY), often citing concerns that substance use or mental health services will attract undesirable or dangerous people and behaviors into their community. [ 12 14 ] Understanding anticipated sentiments of NIMBY targeted at proposed or hypothetical harm reduction programs is crucial to designing informational messaging to garner local support. In this paper, we describe NIMBYism among business owners and employees working in areas of high-drug activity in Baltimore City towards OPS and drug checking, neither of which are currently available, compared to substance use treatment facilities, which are established and operational throughout the city.…”
Section: Introductionmentioning
confidence: 99%